ENERGI ALTERNATIF BIOBRIKET DARI KOMBINASI LIMBAH AMPAS KOPI DAN LIMBAH BAWANG MERAH - Yan El Rizal Unzilatirrizqi D; Wadli Wadli (Jurnal Ilmu Lingkungan, 2022)
Bio-briquettes have become a feasible method for achieving alternative energy and waste utilization goals. The approach of this research is to manufacture bio-briquettes by utilizing Robusta coffee grounds and onion peels with optimal standards obtained from nourishment and agricultural outgrowth in Brebes Regency. In bio-briquettes experiments, a 25% - 75%, 60% - 40% composition ratio of coffee grounds and onion peels was used, and a 50% - 50% composition ratio. The result of the bio-briquettes experiment demonstrate that the ratio of the mixture of 75% coffee grounds and 25% onion peels is the most optimal according to SNI Quality of Wood Charcoal Briquettes  Number 01-6235-2000 with a calorific value of 5000,15 cal/gram, the water content of 6,55%, ash content is 6,8%, the volatile matter is 41,87%, and bG